Internal Control Analysis on Anti-Dumping Duty Exemptions HS 72 in Batam - Kalika Dianti Franconnie (Jurnal Proaksi, 2025)
Main Purpose - This study analyzes the internal control of KPU BC Batam as a Free Trade Zone and Free Port, particularly in relation to Anti-Dumping Duties HS 72.Method - This study provides an in-depth analysis using descriptive qualitative method with NVIVO 15 and literature review.Main Findings - Findings reveal that, despite achieving optimal tax revenue and Organizational Performance Value (NKO), challenges remain, such as limited facilities and infrastructure, low public awareness, competency gaps, particularly in risk management and integrity, system disruptions, increasingly complex smuggling methods and the presence of unregistered ports. Theory and Practical Implications - Strengthened governance, human resources, digital systems and enhanced coordination with relevant authorities are pivotal in mitigating smuggling risks.Novelty - This study extends governance and risk management literature by addressing the oversight challenges related to anti-dumping duty exemptions and proposing solutions to improve inter-agency accountability within Batam Customs and Excise.